2002
DOI: 10.1177/109467002237494
|View full text |Cite
|
Sign up to set email alerts
|

Does Customer Knowledge Affect How Loyalty is Formed?

Abstract: The authors first propose and test a cognitive-affectiveconative baseline model: Perceived service quality (both tangible company-related and employee-related factors) is modeled antecedent to satisfaction and trust, which in turn are antecedents to customer loyalty responses (word of mouth and traditional loyalty). These relationships are then hypothesized to be moderated by high versus low knowledge, a moderation based on central versus peripheral processing. The results show that employee service quality ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
163
1
19

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(203 citation statements)
references
References 52 publications
20
163
1
19
Order By: Relevance
“…The two dimensions of proactive improvement are discriminant at p < 0.001. Additionally, although the correlation of the two constructs is 0.89, the confidence interval around this correlation never includes 1, which provides strong indication for discriminant validity between the constructs (Anderson and Gerbing 1988;Smith and Barclay 1997;Chiou et al, 2002). Further, only very minor crossloadings among the items and the error terms of the proactive cost improvement scale and the proactive performance improvement scale, and vice versa, could be observed.…”
Section: Scale Differentiationmentioning
confidence: 94%
“…The two dimensions of proactive improvement are discriminant at p < 0.001. Additionally, although the correlation of the two constructs is 0.89, the confidence interval around this correlation never includes 1, which provides strong indication for discriminant validity between the constructs (Anderson and Gerbing 1988;Smith and Barclay 1997;Chiou et al, 2002). Further, only very minor crossloadings among the items and the error terms of the proactive cost improvement scale and the proactive performance improvement scale, and vice versa, could be observed.…”
Section: Scale Differentiationmentioning
confidence: 94%
“…Several studies have shown a relationship between satisfaction and loyalty, although a direct relationship is not always postulated [4,5,15,19,23] Agustin and Singh [1] investigated both a direct relationship and one mediated by trust and value. Since there is lack of universal support for this link, it was treated as a weak hypothesis and included as part of additional analysis.…”
Section: Relational Dependence Hypothesesmentioning
confidence: 99%
“…In the general marketing literature [5,14], a correlation was established, though a bad experience may obviously have a negative effect. The relationship between loyalty and word of mouth may not be straightforward, but it seemed worth exploring; thus: H15 Customer loyalty is positively related to word of mouth.…”
Section: Relational Dependence Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Attitudes are a way of summarizing consumer evaluation, so they can provide important information for the marketer because of their direct impact on the use service decision (Longenecker et al, 2005). Nowadays, attitudes are considered multidimensional, with three components (Chiou et al, 2002;Eagly & Chaiken, 2007;Hawkins et al, 2004). Its view that attitude as a construct of three components: cognitive, affective and conative (Chang, 2011;Rosenberg & Hovland, 1995).…”
mentioning
confidence: 99%